2015
DOI: 10.1016/j.yjmcc.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant treatment normalizes mitochondrial energetics and myocardial insulin sensitivity independently of changes in systemic metabolic homeostasis in a mouse model of the metabolic syndrome

Abstract: Cardiac dysfunction in obesity is associated with mitochondrial dysfunction, oxidative stress and altered insulin sensitivity. Whether oxidative stress directly contributes to myocardial insulin resistance remains to be determined. This study tested the hypothesis that ROS scavenging will improve mitochondrial function and insulin sensitivity in the hearts of rodent models with varying degrees of insulin resistance and hyperglycemia. The catalytic antioxidant MnTBAP was administered to the uncoupling protein-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…We observed significantly higher NF‐κB protein and TNF‐α and IL‐6 genes in the hearts of Con(‐) group. Oxidative stress is another cellular signaling component associated with insulin resistance in the heart, and we also observed significant downregulation of the endogenous antioxidant enzymes, SOD2, and catalase, in the hearts of Con(‐) group . Importantly, the severity of all the above changes in the heart was greater in Con(‐) hearts than in HFHFrD group.…”
Section: Discussionsupporting
confidence: 50%
“…We observed significantly higher NF‐κB protein and TNF‐α and IL‐6 genes in the hearts of Con(‐) group. Oxidative stress is another cellular signaling component associated with insulin resistance in the heart, and we also observed significant downregulation of the endogenous antioxidant enzymes, SOD2, and catalase, in the hearts of Con(‐) group . Importantly, the severity of all the above changes in the heart was greater in Con(‐) hearts than in HFHFrD group.…”
Section: Discussionsupporting
confidence: 50%
“…114,151,152 Increased H 2 O 2 resulting from superoxide (O − 2 ) production at complex I has been observed in cardiac mitochondria from obese mice. 44,153,154 During ADP-driven respiration (coupled OXPHOS), H 2 O 2 production was found to be higher in atrial tissue from patients with T2DM, 107 and in obese mice with T2DM, 155 compared with non-diabetic controls. In contrast, lower ROS production was reported in high-fat-high-sugar diet fed rats.…”
Section: Production Of Reactive Oxygen Species In Obesity and T2dmmentioning
confidence: 97%
“…Approximately 90% of cellular ROS is produced in the mitochondria mainly from complexes I and III . Increased H 2 O 2 resulting from superoxide (O2-) production at complex I has been observed in cardiac mitochondria from obese mice . During ADP‐driven respiration (coupled OXPHOS), H 2 O 2 production was found to be higher in atrial tissue from patients with T2DM, and in obese mice with T2DM, compared with non‐diabetic controls.…”
Section: Mitochondrial Structure and Function In The Diabetic Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it remains to be determined if strategies that will directly correct the changes in myocardial insulin signaling described above will reverse heart failure. Oxidative stress is a widely accepted mechanism for cardiac dysfunction in insulin resistant states and it was recently reported that targeted anti-oxidant therapy may partially restore abnormal insulin signaling and improve cardiac structure and function 152 . Combined treatment with polyphenols resveratrol and S17834 also significantly restored cardiac function in diet-induced heart failure in rodent models via multiple mechanisms including reducing oxidative stress, reversing oxidative modifications of proteins, reducing hyperinsulinemia and increasing circulating adiponectin concentrations 153 .…”
Section: Implications For Therapy and Future Researchmentioning
confidence: 99%